Suppressing photorespiration for the improvement in photosynthesis and crop yields: A review on the role of S-allantoin as a nitrogen source. (1st May 2019) - Fahad, Shah; Khan, Faheem Ahmed; Pandupuspitasari, NuruliarizkiShinta; Hussain, Saddam; Khan, Imtiaz Ali; Saeed, Muhammad; Saud, Shah; Hassan, Shah; Adnan, Muhammad; Amanullah,; Arif, Muhammad; Alam, Mukhtar; et al.
Abstract: Environmental variations resulting in biotic and abiotic stresses demand adaptive changes in the photosynthetic machinery. To cope with these challenges, plant scientists are constantly striving to enhance photosynthetic activity. The photorespiration pathway, which fixes O2 and releases CO2 in C3 plants, competes with photosynthesis. One method to increase yield would be to enhance photosynthesis by engineering the photorespiratory pathway. To date, three engineered photorespiratory pathways have been produced, of which two have been proven experimentally in the model plant, Arabidopsis thaliana . These approaches might be helpful in enhancing crop resilience to future environmental challenges. In partially photorespiratory suppressed plants, it is hypothesized that a gene cluster may have formed between bacterial glycolate dehydrogenase ( GDH ), glyoxylate carboligase ( GCL ), and tartronic semi aldehyde ( TSR ) genes with Arabidopsis allantoin degradation genes like Arabidopsis allantoinase ( AtALN ) to utilize S-allantoin as a source of nitrogen. Observations of the use of allantoin as an exclusive source of nitrogen or energy by Arabidopsis and Escherichia coli led us to propose a genetic switch control model between nitrogen assimilation and energy producing pathways in partially photorespiratory suppressed plants. Highlights: Photorespiratory bypass is a potential mechanism to increase photosynthetic yield. GDH, GCL, and TSR genes were utilized to generate photorespiratory bypasses. Allantoin is proposed as a novel N source in photorespiratory suppressed plants. A gene cluster formation for the utilization of systemic allantoin is proposed.